2021
DOI: 10.1039/d0sc07025d
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent communication between multiple amino acids during protein folding

Abstract: Cooperativity is considered to be a key organizing principle behind biomolecular assembly, recognition and folding. However, it has remained very challenging to quantitatively characterize how cooperative processes occur on a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…1). A similar combination of small barriers and transitions requiring maximal cooperativity between amino acids was found for the folding of small proteins 45 . The fluctuation-driven character of the open-closed transition is also evident in nonequilibrium pulling simulations of Phe4 using dissipation-corrected targeted MD 46 .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…1). A similar combination of small barriers and transitions requiring maximal cooperativity between amino acids was found for the folding of small proteins 45 . The fluctuation-driven character of the open-closed transition is also evident in nonequilibrium pulling simulations of Phe4 using dissipation-corrected targeted MD 46 .…”
Section: Discussionsupporting
confidence: 62%
“…A similar combination of small barriers and transitions requiring maximal cooperativity between amino acids was found for the folding of small proteins. 48…”
Section: Discussionmentioning
confidence: 99%
“…Such effects are found when ligands bind to various macromolecules, in particular to receptors, during signal transduction in cell or in the case of intercellular interactions. Although low-molecular-weight ligands do not take part in the processes of protein folding [ 32 , 33 , 34 ] and DNA melting, the latter are substantially cooperative. Thus, cooperativity significantly affects both intracellular and intercellular regulation of life processes [ 25 , 35 , 36 , 37 , 38 ].…”
Section: Statistical Entropy In Description Of Living Systems At the ...mentioning
confidence: 99%
“…χ ij; kl t ð Þ for all the systems using their respective transition paths. 27 The results for the villin and the WW domain are shown as the orange curves in Figure 2B, E. The function χ(t) quantifies the cooperative formation between (i, j) amino acid contact and (k, l) amino acid contact: χ(t) = 0 when these contacts are formed independently, whereas χ(t) > 0 if these contacts are formed cooperatively.…”
Section: Dynamic Cooperativity In Protein Foldingmentioning
confidence: 99%
“…19,20,25,26 In particular, we have demonstrated that simultaneous formation of multiple amino acid contacts is a distinguishing characteristic unique to the folding transition path and that the folding transition state can be identified as the state in which the amino acid correlation is maximal. 27 This was done by analyzing multipoint time correlation function that measures time-dependent cooperativity, termed dynamic cooperativity, between amino acid contact formations. Importantly, the analysis of dynamic cooperativity can be performed solely from the folding transition paths of a single protein, that is, without introducing any mutations.…”
Section: Introductionmentioning
confidence: 99%